Odpowiedź :
a)
y - x = 4
3 (x + y) = 24
y - x = 4
3x + 3y = 24
y = 4 + x
3x + 3(4 + x) = 24
y = 4 + x
3x + 12 + 3x = 24
y = 4 + x
6x = 24 - 12
y = 4 + x
6x = 12 | :6
y = 4 + x
x = 2
y = 4 + 2
x = 2
y = 6
x = 2
b)
x - 2y = 4
x + 3 = 2y
c)
3x - 1 = y - 2
4x - 3 = -2 (y - 2)
3x - 1 + 2 = y
4x - 3 = -2y + 4
3x - 1 + 2 = y
4x - 3 + 2 = 3x -1
3x -1 = y
4x - 1 = 3x - 1
3x -1 = y
4x - 3x = -1 + 1
3x - 1 = y
x = 0
3 * (0) - 1 = y
x = 0
0 - 1 = y
x = 0
-1 = y
x = o
d)
2( x + y ) - ( x + 1 ) = y + 2
x + y = 1
2x + 2y - x - 1 = y + 2
x = 1 - y
2(1-y) - (1-y) = y +2
x = 1 - y
2 - 2y - 1 + y = y + 2
x = 1 - y
1 - y = y + 2
x = 1 - y
1 - 2 = y + y
x = 1 - y
-1 = 2y
x = 1 - y
y = 1/2
x = 1 - 1/2
y = 1/2
x = 1/2
e)
1/2 (x-1) + y = -2 i 1/2
x - 7 = 1 - y
1/2x - 1/2 + y = -2 i 1/2
x = 1 - y + 7
1/2x - 1/2 + y = -2 i 1/2
x = 8 - y
1/2*(8 - y) - 1/2 + y = 2 i 1/2
x = 8 - y
4 - 1/2y - 1/2 + y = 2 i 1/2
x = 8 - y
3,5 - 2,5 = -y
x = 8 - y
1,5 = -y
x = 8 - y
y = -1,5
x = 8 - y
y = -1,5
x = 8 + 1,5
y = -1,5
x = 9,5
f)
x(x - 6) - x(y + x) = y(3 - x)
2x + y = 0
x^2 - 6x - xy - x^2 = 3y - xy
2x + y = 0
x^2 - 6x - xy - x^2 - 3y + xy = 0
2x + y = 0
-6x - 3y = 0
2x + y = 0
y - x = 4
3 (x + y) = 24
y - x = 4
3x + 3y = 24
y = 4 + x
3x + 3(4 + x) = 24
y = 4 + x
3x + 12 + 3x = 24
y = 4 + x
6x = 24 - 12
y = 4 + x
6x = 12 | :6
y = 4 + x
x = 2
y = 4 + 2
x = 2
y = 6
x = 2
b)
x - 2y = 4
x + 3 = 2y
c)
3x - 1 = y - 2
4x - 3 = -2 (y - 2)
3x - 1 + 2 = y
4x - 3 = -2y + 4
3x - 1 + 2 = y
4x - 3 + 2 = 3x -1
3x -1 = y
4x - 1 = 3x - 1
3x -1 = y
4x - 3x = -1 + 1
3x - 1 = y
x = 0
3 * (0) - 1 = y
x = 0
0 - 1 = y
x = 0
-1 = y
x = o
d)
2( x + y ) - ( x + 1 ) = y + 2
x + y = 1
2x + 2y - x - 1 = y + 2
x = 1 - y
2(1-y) - (1-y) = y +2
x = 1 - y
2 - 2y - 1 + y = y + 2
x = 1 - y
1 - y = y + 2
x = 1 - y
1 - 2 = y + y
x = 1 - y
-1 = 2y
x = 1 - y
y = 1/2
x = 1 - 1/2
y = 1/2
x = 1/2
e)
1/2 (x-1) + y = -2 i 1/2
x - 7 = 1 - y
1/2x - 1/2 + y = -2 i 1/2
x = 1 - y + 7
1/2x - 1/2 + y = -2 i 1/2
x = 8 - y
1/2*(8 - y) - 1/2 + y = 2 i 1/2
x = 8 - y
4 - 1/2y - 1/2 + y = 2 i 1/2
x = 8 - y
3,5 - 2,5 = -y
x = 8 - y
1,5 = -y
x = 8 - y
y = -1,5
x = 8 - y
y = -1,5
x = 8 + 1,5
y = -1,5
x = 9,5
f)
x(x - 6) - x(y + x) = y(3 - x)
2x + y = 0
x^2 - 6x - xy - x^2 = 3y - xy
2x + y = 0
x^2 - 6x - xy - x^2 - 3y + xy = 0
2x + y = 0
-6x - 3y = 0
2x + y = 0